Key comparison CCQM-K59 : determination of nitrite and nitrate in calibration solutions. Final report - Máriássy, M. (2008)
In this key comparison anion calibration solutions of nitrate and nitrite were investigated. The mass fractions of the anions in both solutions were about 1 g/kg. For the nitrate comparison 8 participants provided results; 3 analytical techniques were used: ion chromatography, capillary electrophoresis and coulometry after ion exchange. The nitrite amount content was determined by 7 participants using one of the following 3 techniques: ion chromatography, titrimetry, and capillary electrophoresis. The following institutes participated in this key comparison: INTI (Argentina), KRISS (Korea), LNE (France), NIM (P.R.China), NIST (USA), NMIJ (Japan), SMU (Slovakia), and VNIIM (Russia). The variability (RSD) of the results is about 0.75% for both the nitrite and the nitrate solutions. Compared to the key comparison CCQM-K29 the results of CCQM-K59 were significantly worse. This is in part due to the measurement methods used, possibly also due to the standards used by the institutes. A pilot study (P89) was performed in parallel on the same calibration solutions used in this K59 comparisons study by laboratories preferring to participate in the pilot study and on a seawater sample containing about 0.1 mg/kg nitrite and 1 mg/kg nitrate. The results of the pilot study are reported separately.